Error Analysis In The Post Test Of Writing Post Basic Written By The First Semester Of English Department - Theresia Budi Sucihati; Asmara Nengke Anggiamurni (International Journal of Education, Vocational and Social Science, 2022)
The objective of this study is to analyze the grammatical errors in students’ writing. The researcher is doing this research because most English Department students still make mistakes when writing a composition in English. The type of study was descriptive qualitative research. This study is done by classifying and analyzing the students' written texts, their interviews, and the teacher's interviews. The grammar categories to be analyzed were subject-verb agreement errors, verb-tense errors, verb-form errors (singular and plural errors), and word-form errors. The data analysis revealed that word-form errors were the most common, and singular/plural noun forms were the least frequent.The students' problems stemmed from the influence of their first language, their habit of speaking English, and their lack of care in rereading their compositions. Keywords: Grammar, Error analysis, Writing.